Meningkatkan Hasil Belajar Siswa Melalui Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation - Gusmawati Gusmawati; Zainuddin Zainuddin; Mustika Wati (Universitas Lambung Mangkurat, 2013)
Conventional learning makes students more dependent on teachers, less active students participation in the learning process cause low mastery of learning results. Therefore, the aim of the research is to describe the effectiveness of the implementation of cooperative learning model Group Investigation type in improving student learning results. In particular, this study aimed to describe: (1) the implementation of the lesson plan, (2) the learning results after implementation of cooperative learning model Group Investigation type, (3) social skills of students, (4) the response of students towards learning. The type of the research is a class action research. This research consist of three cycles, each cycle includes the plan, action/observation, and reflective. Devices and instruments used in this research is the lesson plans, handouts, worksheets, THB, observation sheets of lesson plan implementation, and social skills of students, and student response sheets. Data follected through tests, observations, questionnaires, and documentation. The results showed that (1) lesson plan implementation in the first cycle was 76.00%, the second cycle is 84.00% and the third cycle was 99.33%. (2) mastery in the classical student learning results in the first cycle was 63.33%, the second cycle was 80.00%, and the third cycle is 100%. (3) students' social skills for active listening skills have an average percentage of each cycle for 86.67%, 83.33% argued for asking question was 90.83% and 84.16% for active discussion. (4) the general student response was good. In the conclusion, cooperative learning model Group Investigation type effective in improving student learning results in class XI IPA 1 SMAN 4 Banjarmasin on the subject of static fluida.